High levels of cardiac and oxidative stress biomarkers ameliorated following treatment with aspirin, vitamin C, and Justicia secunda hydromethanol leaf extract on epinephrine induced-myocardial infarction in male Wistar rats - Mobisson, Samuel K.; Wopara, Iheanyichukwu; Monye, Justin B.; Iyanyi, Uchechukwu L.; Izunwanne, Desmond; Obemebe, Agona O. (International Journal of Basic & Clinical Pharmacology, 2025)
Background: Myocardial infarction is an increasing cardiac disorder globally. This study investigated the ameliorative potentials of Justicia secunda hydromethanol leaf extract on epinephrine-induced myocardial infarction in male Wistar rats. Methods: Twenty-four rats weighing (70-170 gm) were assigned into 6 groups (n=4). Group A was control, group B received epinephrine (0.08 mg/kg) intraperitoneally for 2 days; groups C-F received epinephrine followed by oral treatments: Aspirin (2 mg/kg), Justicia secunda (1 mg/kg), Justicia secunda (2 mg/kg) and vitamin C (2 mg/kg) respectively for 14 days. Results: There was a significant elevation of lactate dehydrogenase and troponin T and disruption in electrolyte balance, indicative of myocardial injury. Treatment with Justicia secunda (2 mg/kg), aspirin, and vitamin C significantly reduced LDH and troponin T levels (p<0.01), improved antioxidant status (increased SOD, CAT, GSH; decreased MDA), and slightly normalized electrolytes. Justicia secunda (2 mg/kg), exhibited improvement in high-density-lipoproteins and reduction in low-density-lipoprotein levels. Conclusions: Treatment with Justicia secunda (particularly at 2 mg/kg), aspirin, and vitamin C ameliorated the epinephrine-induced myocardial infarction. Hence, if these results apply to humans, using Justicia secunda in management of myocardial infarction and oxidative stress should be encouraged as a potential natural adjunct.